Parenting Styles Parental Employment Child Independence Among Elementary Students: Pola Asuh Status Pekerjaan Orang Tua Dan Kemandirian Anak Sekolah Dasar - Agustina, Ayunda Dwi; Indanah, Indanah; Yulisetyaningrum, Yulisetyaningrum (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Child independence is a crucial developmental aspect during the elementary school period and is closely associated with family-related factors. Specific Background: Parenting styles and parental employment status are frequently discussed determinants that shape children’s ability to manage daily activities and responsibilities independently. Knowledge Gap: Despite extensive discussion, empirical evidence examining the combined association of parenting styles and parental employment status with child independence within a specific elementary school context remains limited. Aims: This study aimed to analyze the relationship between parenting styles and parental employment status with the level of independence among school-aged children at SD 2 Jurang, Gebog District, Kudus Regency. Results: Using a quantitative correlational design with a cross-sectional approach and total sampling of 49 students aged 9–12 years, Chi-Square analysis revealed a statistically significant relationship between parenting styles and child independence (p < 0.05) with strong association strength, while parental employment status also showed a significant relationship with moderate association strength. Novelty: The study integrates parenting styles and parental employment status simultaneously within a single elementary school setting to explain variations in child independence. Implications: These findings provide empirical support for parents and schools to consider parenting approaches and work-related conditions when supporting the development of independence among elementary school children. Highlights • Democratic caregiving patterns were predominantly associated with higher self-reliance levels.• Work-related parental conditions showed a measurable association with children’s daily autonomy.• Most participants demonstrated moderate autonomy within academic and home activities. KeywordsParenting Styles; Parental Employment Status; Child Independence; School-Age Children; Elementary School